Pengembangan Aplikasi PKL Track Berbasis Android untuk Monitoring Praktik Kerja Lapangan di SMKS Muhammadiyah Mentok - Jinan Khalishah; Linda Fujiyanti; Vivin Mahat Putri (Jurnal Inovasi Teknologi Terapan, 2026)
The Internship Program (PKL) at SMKS Muhammadiyah Mentok faces several challenges, one of which is that the processes are still carried out manually, such as submission, attendance, daily reports, and scheduling of evaluation and monitoring for students. This condition often leads to errors and inefficiency. PKLTrack is an Android-based application developed as a solution to these problems, In this system development, several main features are included, such as online internship submission, GPS- and geofencing-based attendance equipped with selfies, daily report submission, evaluation and monitoring schedule notifications, and direct assessment by partner institutions. This study adopts the prototype method, with data collection techniques including interviews, observations, and literature studies for needs analysis. The User Acceptance Testing (UAT) was conducted on 30 students and resulted in an 87% success rate, indicating that the system is highly feasible to be used as a monitoring solution. The results show that PKLTrack can improve effectiveness, efficiency, and discipline in the implementation of the internship program.